TYPE TRAITS AND MILK YIELD GENETIC PARAMETERS AND BREEDING VALUES OF HOLSTEIN IN IRAQ - Adnan Jabbar Jadoa (Basrah Journal of Veterinary Research)
In this study a total of 928 Holstein cows daughters of 33 sires bred at Al-Naser Dairy Cow Station (60 km south of Baghdad) were used to appraisal the final score for the 14 linear type traits: rear udder height (RERUDHIH), teat length (TETLENGT), strength(STRENGTH), dairy form (DAIRYFOM), rump angle (RUMPANGL), body depth (BODYDEP), fore udder attachment (FORUDER), teat placement (TETPLACM), udder depth (UDERDEPT), udder suspension (UDERSUSP), rear udder width (RERUDWID), rear leg set (RLSET), foot angle (FOTANGLE) and rump width (RUMPWIDT). Heritability of type traits ranged from 0.080 to nearly one, and different methods did not exhibit high variability in heritability estimates for each trait. Age showed significant affect on BODYDEPT and TETPLACEM. Day in milk showed significant effect on TETLENGT, STRENGTH and UDDERDEPT. The genetic correlation among type traits ranged from -0.724 to 0.904. It was positive and high between milk yield and RERUDERWIDT, RUMPANGL and TETLENGT. However, milk yield negatively correlated with UDERDEPT and RLSET. The breeding values for sires in deferent traits ranged from -7.656 to 8.868, and showed a high variability among sires for each trait in this study